Faktor-faktor yang Berhubungan dengan Kejadian Kekurangan Energi Kronik (KEK) Pada Ibu Hamil di Puskesmas Gandus Palembang Tahun 2021 - Peni Sukma Negara; Diah Sukarni; Sendy Pratiwi Rahmadhini (Universitas Batanghari Jambi, 2022)
Based on the data from Palembang Health Office, the number of maternal mortality from 2018-2020 was 4, 3 and 3 women respectively (Palembang Health Office, 2020). Maternal mortality is caused by bleeding, anemia, CED, and other complications. Based on the data in 2018 the number of pregnant women who experienced CED was 18.2% and 20.2% in 2019 (Sumatera Selatan Provincial Health Office, 2019). The CED incidence in pregnant women is influenced by some factors such as the amount of daily energy intake, parity, maternal age, maternal knowledge, family income, and dietary restrictions (Yuliastuti, 2014). Based on the medical record data at Gandus Palembang Health Center, in 2018, there were 1303 pregnant women who visited for antenatal care, with 4.5% or 59 pregnant women suffered from CED. In 2019, from 1179 pregnant women, 144 (12.2%) suffered from CED. In 2020, from 1151 pregnant women, 128 (11.1%) suffered from CED. This study aimed to find out the correlation between Parity, Maternal Age and Knowledge with Chronic Energy Deficiency Incidence in pregnant women. This quantitative study used an analyticalsurvey method with cross sectional approach. The population in this study was all 50 pregnant women who visited Gandus Public Health Centre for Antenatal care in 2021. The sample data were collected by means of Accidental Sampling Method. From univariate data analysis, it was found that the number of pregnant women who suffered from CED was high with 68% or 34 respondents, high risk parity with 62% or 31 respondents, high risk maternal age with 62% or 32 respondents and low knowledge with 64% or 21 respondents. From bivariate analysis using Chi-Square test, it was found that there was a correlation between Parity (p-value 0.001), Maternal Age (p-value 0.018) and Knowledge (p-value 0.000) with Chronic Energy Deficiency Incidence in pregnant women at Gandus Public Health Centre. It was concluded that there was a correlation between Parity, Maternal Age and Knowledge with Chronic Energy Deficiency Incidence in pregnant women at Gandus Public Health Centre in 2021. It is recommended that health personnel in Gandus Public Health Centre provide more information about Chronic Energy Deficiency Incidence in pregnant women.Â